Research Title: Virginia Woolf and Identity As established in “Mrs Dalloway” and “To the Lighthouse” - Ragaa Hamed Ahmed Omer (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية, 2024)
Virginia Woolf, a prominent modernist has contributed significantly in the development of the modern novel by the end of the 19th century and it’s indulged of psychology. Woolf was very much interested to connect her art with identity. This research paper aims to investigate the multiple dimensions of Identity as presented in Virginia Woolf’s novels Mrs Dalloway (1925) and To the Lighthouse (1923). She has started her journey in establishing identity by employing various framing devices such as the use of mirrors, portraits, dinner parties. She had manipulated these devises in order to acknowledge what she called it “a solid, visible and structured reality within a frame of shifting, invisible and unstructured reality outside it”. She synthesized these devises functioning inward and outward and this continuous motion enabled her to overshadow the contradictory elements in her expression of identity. The paper discusses Virginia Woolf ‘s establishing journey of identity in Mrs Dalloway and To the Lighthouse. The approach adopted here is analytical and descriptive approach. The study concluded that identity as established in Virginia Woolf ‘s novels presented in multiple types such as social identity, temporal identity and Gender identity that made readers so much interested in reading her innovative art.